Antimicrobial effect of anesthetic‐eluting ultra‐high molecular weight polyethylene for post‐arthroplasty antibacterial prophylaxis. Issue 4 (20th March 2019) - Gil, Dmitry; Grindy, Scott; Muratoglu, Orhun; Bedair, Hany; Oral, Ebru
ABSTRACT: Despite being a relatively safe surgery, total joint replacement is often associated with two major complications—severe post‐operative pain and periprosthetic joint infection. Local sustained delivery of therapeutics to the surgical site has a potential to address these complications more effectively than current clinical approaches. Given that several analgesics were shown to possess antibacterial activity, we propose here to use analgesic‐loaded ultra‐high molecular weight polyethylene (UHMWPE) as a delivery vehicle to provide antimicrobial effect after an arthroplasty. Three commonly used anesthetics, lidocaine, bupivacaine, and ropivacaine, were analyzed in order to reveal the drug with the highest antibacterial activity against methicillin‐sensitive Staphylococcus aureus . Having shown highest antibacterial activity in the bacterial susceptibility tests, bupivacaine was chosen to be incorporated into UHMWPE to provide antibacterial properties. Bupivacaine‐loaded UHMWPE possessed moderate dose‐dependent antimicrobial properties, decreasing the S. aureus proliferation rate by up to 70%. Biofilm formation was also substanitally inhibited during the first 9 h of culture as quantified by bacterial counts and SEM. This proof‐of‐concept study is first of its kind to demonstrate that analgesic‐loaded UHMWPE can be used as part of a multimodal antimicrobial therapy. © 2019 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res Abstract : Total joint replacement is often associated with two major complications – severe post‐operative pain and periprosthetic joint infection. Here we propose local sustained delivery of therapeutics to the surgical site using UHMWPE joint implants. Given that some commonly used analgesics possess antibacterial activity we hypothesize that analgesic‐loaded UHMWPE can provide post‐arthroplasty pain relief and antibacterial prophylaxis.